PENERAPAN IN HOUSE TRAINING UNTUK MENINGKATKAN KOMPETENSI GURU TENTANG KONSEP MATEMATIKA DI SMP NEGERI 10 BOGOR - Estiza Septiana (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
APPLICATION OF IN-HOUSE TRAINING TO IMPROVE TEACHER COMPETENCE ON MATHEMATICAL CONCEPTS IN JUNIOR HIGH SCHOOLThis research departs from the phenomenon that occurs in schools that the teacher's low understanding of the concept of Mathematics in the learning process. Therefore, a school principal needs to consider a strategy to increase teacher competency skills so that they can improve their abilities. This study aims to determine the effectiveness of the implementation of in-house training in improving teacher competence on the concept of Mathematics, to describe the process of increasing teacher competence about the concept of Mathematics through the implementation of in-house training activities, to measure the magnitude of the increase in teacher competence on the concept of Mathematics through the implementation of in-house training. The research was conducted at SMP Negeri 10 Bogor in the first semester of the 2019/2020 academic year. The results of this study indicate that by implementing in-house training can motivate teachers to improve their competence in understanding mathematical concepts. Before carrying out the in-house training, of the 5 Mathematics teachers, almost all of the teachers did not have the correct understanding of the concept of Mathematics learning. After the in-house training on the concept of learning Mathematics, there was an increase in the first cycle as many as 3 teachers (60%) became aware of the concept of Mathematics, as many as 1 person (20%) understood enough, and as many as 1 person (20%) did not understand. In the second cycle there was an increase to all teachers, as many as 5 people (100%) understood the concept of learning Mathematics. That the implementation of in-house training can improve the competence of teachers about the concept of Mathematics. Therefore, researchers suggest that the implementation of In house training in improving teacher competence should be socialized and used as an alternative in understanding Mathematics concepts for teachers in the Bogor City Education Office.